Mismanagement of Human Capital at Campus X in Medan - Hantono Hantono; Rosnida Rosnida; Dody Arisandy; Sri Milfayetty; Zainuddin Zainuddin; Zuraida Lubis (Eduvest - Journal of Universal Studies, 2024)
This study explores the critical role of universities in higher education, emphasizing their scientific orientation and societal impact. The investigation covers the importance of human capital and leadership in educational institutions, using Sisingamangaraja University in Medan, Indonesia, as a case study. The university's challenges, including radical student activities and ineffective human capital management, highlight the need for comprehensive strategies in leadership and human capital development. Through a qualitative approach and SWOT analysis, this research aims to provide insights into effective educational management and the implications of its failures.